Superparamagnetic Adsorbent for Removal of Uranium in Groundwater, South Korea - Husnain, S. M.; Hm, W.; Chang, Y- S. (The Nucleus, 2019)
The feasibility of magnetic adsorbent (P-Fe-CMK-3) for the removal of uranium using column based adsorption study has been performed. The synthesized material is efficient to capture natural uranium from groundwater. The Phosphonate and UO2 2+ interactions were responsible for uranium adsorption. This study confirmed the removal of natural uranium from groundwater (with initial uranium concentration around 107 ppb) within 10 min of contact time. However, the uptake values were not as high as compared to the values observed in batch study due to small contact time between adsorbent and the contaminant. Based on these results, the adsorbent material could be used in large scale treatment of uranium contaminated groundwater and waste streams including domestic uranium filters.